Diagnóstico de los procesos de integración económica de Colombia: Una revisión al tema ambiental. - Sandoval Guzmán, Angie Natalia (Universidad Antonio Nariño, 2023)
International trade has faced a significant environmental challenge worldwide in recent decades. The increase in production and transportation of goods and services to meet growing demand has generated a series of problems (Castillo, 2012). Among them are the increased emission of greenhouse gases, the degradation of air, water, and land quality, deforestation, and biodiversity loss (Castillo, 2012).